Reliability Prediction and Maintenance Interval Planning - Fayzimatov Ulugbek Bahodirovich; Ergashev Xusniddin Muxammadjon oʻgʻli (Genius Journals, 2022)
In this article, reliability prediction and planning of maintenance intervals .
Keywords: Vibroacoustics; Reliability; Electrically; Pneumatically